The influence of mouth breathing on skeletal and dental features of splanchnocranium - (:unkn) unknown (COMENIUS UNIV, 2021)
OBJECTIVE: This study was performed to investigate changes in dentofacial characteristics associated with mouth breathing (MB) and adenoidectomy. BACKGROUND: MB is considered to be an etiological factor of malocclusion. Adenoidectomy is supposed to have the ability to prevent the development of dentofacial deformities. METHODS: This retrospective study included 123 patients, namely 57 nose breathers, 19 former mouth breathers, who have undergone adenoidectomy, and 47 mouth breathers. The groups were compared according to their skeletal and dental characteristics. The measurements of each individual were obtained from lateral cephalograms and dental casts. The comparison was done using one-way ANOVA, Bonferroni post-hoc, Mann-Whitney U and Kruskal-Wallis tests. The statistically signifi cant difference was defi ned as p<0.05. RESULTS: The MB group showed an increase in ArGoMe (p=0.02) angle. No difference was found in the sagittal parameters among the groups. Upper dental arch compression was positively correlated with MB (p=0.00), even in adenoidectomy cases (p=0.01). CONCLUSION: MB alters the vertical and transverse growth of the craniofacial complex. It is associated with longer lower anterior facial height and decreased maxillary intermolar distance. However, it does not infl uence the sagittal parameters. Airway clearance via adenoidectomy promotes the normalization of vertical parameters (Tab. 1, Fig. 2, Ref. 20). Text in PDF www.elis.sk
Keywords: mouth breathing; malocclusion; craniofacial growth; adenoidectomy; cephalometrics; ARCH MORPHOLOGY; CHILDREN